Jail Officers’ Perceptions of the Work Environment in Traditional Versus New Generation Facilities - Applegate, Brandon K. (American journal of criminal justice, 2007)
New Generation jails have emerged as an important innovation in local incarceration. The results of existing research suggest that new generation jail design and operation can positively impact inmates and staff, but the literature is far from unequivocal. The current study utilized data collected from a single jail complex to provide a unique test of how the type of facility influences jail staff perceptions of the work environment along several dimensions. Our results revealed few differences between correctional officers working in traditional units and those posted in new generation units. We discuss the implications of these findings, including the use of direct supervision inmate management in traditional as well as new generation jails.